ACCLIMATIZATING TECHNIQUES OF TOMATO ANEMONEFISH (AMPHIPRION FRENATUS BREVOORT, 1856) BROOD STOCKS - Loc, Ha Le Thi; Van, Phan Thi Hong (Vietnam Journal of Marine Science and Technology, 2009)
Tomato  Anemonefish  (Amphiprion  frenatus)  brood  stocks  from  the  wild were able to adapt and breed in capture condition. The results from experiments showed that temperature,  salinity  and  presence  of  Magnificent  Sea  Anemone  (Heteractis  magnifica) closely related to ability of spawning, re-spawning of the brood stocks as well as egg adhesion to collectors. In stable condition of 26 0 C with the presence of the Magnificent Sea Anemone, at salinity of 33 - 35‰, the brood stocks started spawning after 51 days of acclimatization. The  brood  stocks  spawned  twice  monthly  in  average  and  re-spawned  after  3  to  5  days. Embryonic development on the collectors lasted 5 to 9 days. At salinity of 27 to 29‰, the re-spawning  time  lasted  5  to  9 days,  the  embryos  were  completely  de-adhesive  from  the collectors  after  9  days  of  spawning.  At  salinity  of  40  to  42‰,  the brood  stocks  stopped spawning.